Capturing history : [videorecording (DVD)] the photography of Charles A. Libby, Frank S. Matsura, Frank Palmer (KSPS, 2019)
"At the turn of the twentieth century, three very different photographers worked and lived in the Inland Northwest: Charles A. Libby, Frank S. Matsura, and Frank Palmer. Charles Libby photographed Spokane at a time of great change. For six decades, Libby and his son, Charles Jr., documented the city's rapid growth. It's hard to imagine Spokane's early history without visualizing a Libby photograph. In the Okanogan Valley, photographer Frank Matsura, a Japanese immigrant, was befriended by a community of cowboys, miners, merchants and Native Americans. In a time when portraits were stiff formal affairs, Matsura's photographs seemed to capture a more authentic image of his friends and neighbors. Then there's Frank Palmer, whose love of nature is captured in his beautiful handpainted photographs. Palmer's exotic wilderness photographs were used as postcards by the Spokane Chamber of Commerce to promote tourism to the Inland Northwest."-- back cover